Women’s Leadership and Career Motivation in the Construction Industry: Challenges and Barriers - Alias, Umi Aida; Mohammad, Mimi Mohaffyza; Mafarja, Nofouz; Mohd Nusa, Fatin Najwa (Journal of Technical Education and Training, 2025)
The construction industry is one of the sectors with high employment risks and is closely associated with challenging careers. "Dirty, Difficult, and Dangerous" or 3D describes the work situation on construction sites, making these jobs both difficult and risky. This environment creates problems such as negative organizational culture, difficulty maintaining positions within organizations, hazardous workplace conditions, gender stereotypes, and the overall image of the construction industry, which often deters women from pursuing careers in this field. This study aims to examine the challenges and barriers faced by women in leadership roles in the construction industry and how these factors impact their career motivation. The study focuses on three main objectives: identifying the challenges women leaders face in enhancing career motivation, identifying the obstacles to women’s leadership, and understanding the relationship between these challenges and obstacles in the construction industry. To achieve these objectives, this study employs a literature review and quantitative methods, involving female leaders working in Grade 7 (G7) construction companies who hold positions such as site supervisors, site engineers, architects, safety supervisors, and surveyors. Conducted in the construction area of Johor Bahru, the study surveyed 172 women leaders. Descriptive and inferential analyses were used to measure the variables set in the study. The findings indicate that the primary challenges for women in leadership are organizational culture, maintaining positions within organizations, and gender stereotypes. Additionally, significant barriers include career balance and skill competence. This study serves as a reference for understanding the obstacles and challenges that women leaders face in the construction industry, providing insight into how these barriers can be overcome to enhance women’s leadership and career motivation in this demanding field.